Factorial planning and economic evaluation of the biodiesel production process from swine fat (Research, Society and Development, 2020)
The economic study is an essential parameter within a process, from this, it is possible to define the viability of producing a specific product. The preservation of the environment is one of the major concerns of the last decades, and it is increasingly sought by alternative sources of energy and sustainable development. One of the solutions found is the use of biofuels, as it treats fuel based on renewable sources, they can contribute to the global slowdown. The object of study in this research was the production of biodiesel from swine fat, via acid and basic transesterification, by methyl and ethyl route, seen as this main raw material favorable resources, in addition to having an offer available in the Northeast region, such as which it is often discarded inappropriately to the environment. The experiments were designed according to a factorial design and in these cases, detecting biodiesel with a 1: 3 molar ratio (swine fat: alcohol) via methyl route, with a yield of 97.23%. An ethylic route does not present satisfactory results for transesterification, however, it is still in the testing phase, aiming to obtain lower proportions between the inputs used, using the lowest costs. After a process cost analysis, relating production inputs and energy consumption, there was a better efficiency of the process in relation to the product generated by the methyl route, when used by the ethyl route.